Native microbial consortia: A sustainable strategy for improving the quality of forest seedlings in the Peruvian Amazon - Amaringo Cordova, Luiz Paulo (2025)
Forest plantations represent an alternative to reduce timber extraction pressure in the Amazonian forests. In order to tolerate the hostile field conditions of deforested areas, high-quality seedlings are required. This study aimed to find the optimal dose of a native microbial consortium (NMC), which enhances seedling quality indicators, in three forest species at nursery phase. A completely randomized design (3 × 5) was used. Factor 1: Bolaina blanca (Guazuma crinita Mart.), Capirona (Calycophyllum spruceanum Benth. Hook. f.), and Marupa (Simarouba amara Aubl.). Factor 2: Incremental doses of 0, 160, 320, 480, and 640 mL NMC per plant. The nursery survival (%), robustness index, root height/length ratio, shoot–root index, Dickson Quality Index (DQI), Nitrogen (%), Phosphorus (%), and Potassium (%) content in tissues were analyzed. Statistical analyses consisted of two-way ANOVA per variable and correlation analysis. The results indicated that increasing doses of NMC did not improve nursery survival for any species; did not decrease the robustness index, plant height/root length ratio, or the shoot–root index for any species; and did not increase the DQI, P%, or K% for any species; however, they did increase the N% for all species. In conclusion, the incremental dose of 160 mL was chosen for increasing the N% without affecting nursery survival.